Altered oxidative stress in overtrained athletes - Tanskanen, M.; Atalay, M.; Uusitalo, A. (Journal of Sports Sciences, 2010)
The purpose of the present study was to examine the relationship between oxidative stress and overtraining syndrome. Indicators of oxidative stress (plasma protein carbonyls, nitrotyrosine, and malondialdehyde) and antioxidant status (oxygen radical absorbance capacity) were measured in severely overtrained (two women, five men) and control athletes (five women, five men). Samples were collected from both groups at baseline (i.e. in the overtraining state of overtrained athletes) and after 6 months of recovery, both at rest and immediately after an exercise test to volitional exhaustion. At baseline, overtrained athletes had higher plasma protein carbonyls at rest than controls (mean difference 0.03 nmol · mg-1, 95% CI = 0.01-0.05 nmol · mg-1, P = 0.003, effect size = 0.40). Both at baseline and after recovery, exercise to exhaustion led to an increase in oxygen radical absorbance capacity and malondialdehyde (P = 0.001-0.006) in the controls but not in the overtrained athletes. Furthermore, at baseline, only overtrained athletes showed negative correlations between oxygen radical absorbance capacity at rest and protein carbonyls after exhaustive exercise (r = -0.98, P = 0.0001). These results suggest that increased oxidative stress has a role in the pathophysiology of overtraining syndrome. The attenuated responses of oxidative stress and antioxidant capacity to exercise in the overtrained state could be related to an inability to perform exercise effectively and impaired adaptation to exercise.